Feminism and Film - Humm, Maggie (Edinburgh University Press, 1997)
This is the first study to apply a broad range of theory to contemporary film. With dazzling insight and critical aplomb Maggie Humm highlights and explains feminist issues and offers a fascinating array of original film analyses.